(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: Continuous oral anti-coagulant treatment has been used to reduce the threat of thromboembolism for further than half a century, dragging the lives of thousands of cases. There is increased risk of haemorrhage doing dental procedures in patients on anticoagulant and antiplatelet therapy. Objective: To evaluate the post extraction bleeding rate for oral surgery carried out under continued anti- platelet therapy with clopidogrel. Methods: This prospective observational study was carried out in the department of ’Oral and Maxillofacial (OMF) Surgery’, Military Dental Centre (MDC), Dhaka. A total of 35 patient’s maintenance once daily low dose clopidogrel were purposely selected for this study. The extraction procedure under local anesthesia using 2% lidocaine with 1:1,00,000 epinephrine were done traumatically. A gelatin sponger piece was put down in socket and shut by atraumatic silk. The patients were instructed to apply pressure pack with sterile gauze for within 30 mins. Timing of haemostasis was done in every 9.5 minutes for within 30 minutes. Results: Among 35 patients, mean age was 52.3±10.1 with age range 35 to 69 years. Male patients were predominant (60.0%) with male:female ratio was 1.5:1. Simple extraction was done in 29 patients while rest extractions were done surgically. Majority 22(62.9%) of the patients were managed by pressure pack with gelatin sponge while 15(42.9%) patients were managed by pressure pack only. Regarding post extraction bleeding, majority of the cases haemostasis (91.4%) was achieved within 9.5 minutes after teeth extraction while only 3(8.6%) patients haemostasis 19 to 28.5 minutes after teeth extraction. Conclusion: The study concluded that majority of the patients were managed pressure pack with gelatin sponge and most of the patients had post extraction bleeding time 9.5 minutes. Minor oral surgery can be carried out safely under continued mono antiplatelet therapy with clopidogrel. JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 28-30